Wydział Pomiarów Urzędu Wojewódzkiego Pomorskiego w Bydgoszczy w łatach 1945-1950 (Kronika Bydgoska, 2012)
The structures of the geodesic service reactivated in Poland in 1945 - on the voivodeship level - were located within voivodeship offices in the form of surveying departments. The Bydgoszcz Surveying Department started to operate in the middle of the year 1945, and engineer Modest Kamieński became the department’s head. The department’s main course of actions in Pomorskie Voivodeship included: finding dispersed survey-cartographic documentation, reproduction of damaged parts of land cadaster, stock-taking of geodetic control network points, taking distance and height measurements of municipal centres, supervision over the lower level geodesic service and certified land surveyors, and initiation of geodesic personnel education. In spite of the difficult post-war conditions, the lack of skillcd personnel and Iow salaries, the results of the actions of the Bydgoszcz Surveying Department should be assessed positively.